Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1042/0264-6021:3550179
|View full text |Cite
|
Sign up to set email alerts
|

Exonic Sp1 sites are required for neural-specific expression of the glycine receptor β subunit gene

Abstract: The gene encoding the beta subunit of the inhibitory glycine receptor (GlyR) is widely expressed throughout the mammalian central nervous system. To unravel the elements regulating its transcription, we isolated its 5' non-coding and upstream flanking regions from mouse. Sequence analysis revealed significant differences between the 5' region of the beta subunit gene and the corresponding regions of the homologous GlyR alpha subunit genes; it also identified a novel exon (exon 0) that encodes most of the 5'-un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…A recent article published in FASEB (Ge et al, 2004) showed that one tsp within the human BACE gene promoter was 224 nt upstream and a second tsp was 376 nt further upstream of the basal promoter. An earlier report by Tintrup et al (2001) made similar observations and suggested on the basis of this and other reports cited that tsps remotely situated relative to the basal promoter are characteristic of promoters with multiple Sp1 sites embedded in this region.…”
Section: Discussionsupporting
confidence: 69%
“…A recent article published in FASEB (Ge et al, 2004) showed that one tsp within the human BACE gene promoter was 224 nt upstream and a second tsp was 376 nt further upstream of the basal promoter. An earlier report by Tintrup et al (2001) made similar observations and suggested on the basis of this and other reports cited that tsps remotely situated relative to the basal promoter are characteristic of promoters with multiple Sp1 sites embedded in this region.…”
Section: Discussionsupporting
confidence: 69%
“…Sp1 and Sp3 are thought to be ubiquitously expressed, but these factors have also been implicated in cell typespeciWc regulation of several genes (Heicklen-Klein and Ginzburg 2000; Tintrup et al 2001;Valin et al 2009). Furthermore, the level of Sp1 expression may be highly variable between tissues, as has been shown in developmental studies in mice (SaVer et al 1991).…”
Section: Discussionmentioning
confidence: 93%
“…The p39 promoter lacks sequences resembling common core promoter elements such as initiator, DPE or BRE, which are present in many TATA-less promoters (for example the p35 promoter [11]) [21] REF. Multiple transcription start sites are a common feature of TATA-less promoters, and are found frequently in promoters of cell-type specific genes [2224]. …”
Section: Resultsmentioning
confidence: 99%
“…Although Sp1 and Sp3 are ubiquitously expressed, these transcription factors have been implicated in cell type-specific regulation of several genes in neurons [24, 31, 32]. We have previously reported that a repeated GC box that binds Sp1, Sp3 and Sp4 in vitro is necessary and sufficient for neuron-specific expression of the cdk5 regulator p35 [11].…”
Section: Discussionmentioning
confidence: 99%